Depression аnd Cardiovascular Diseases: Cause, Consequence оr Comorbidity - Katerenchuk O. (Львівський клінічний вісник)
Introduction. According to the World Health Organization (WHO) Report currently more than 350 million people in the world suffer from clinically significant anxiety and depressive disorders and this number is expected to grow. Depression is the leading cause of disability worldwide. The special attention should be given to the category of patients with the cardiovascular diseases, because the existence of depression greatly deteriorates the disease course. It is well-known that depression and anxiety are the risk-factors for the development of cardiovascular diseases. Also depression is usually observed in patients in early post-myocardial infarction period, in patients with hypertension, especially with the heart failure syndrome. Aim. To analyze the literature sources and to propose own thoughts on the topic of the depression and cardiovascular diseases, their causes, consequence or comorbidity. Materials and methods. Content analysis, method of system and comparative analysis, bibliosemantic method of research of actual scientific researches on the topic of the depression and cardiovascular diseases, their causes, consequence or comorbidity was made. Results and discussion. The combination of depression and cardiovascular diseases is a well-known clinical fact, supported by the results of many clinical studies. Since the 90’s more than 100 descriptive studies in this field assessing the relationship of depression with cardiovascular morbidity and mortality have been performed. Also more than 60 prospective studies were conducted to establish the connection between the presence of depression and coronary heart disease. It is important to note that the negative impact on the prognosis has not only the so-called major depression, but also its mild form. Women are 1.7 times more likely to experience a significant depression than men. The majority of clinical studies of depression in patients with heart failure do not provide a separate data for men and women. One study analyzed the prevalence of depression in patients with heart failure only in out-of-hospital settings. The symptoms of depression were observed in 64 % of the women and 44 % of the men. Interestingly, the hospitalization for treatment of acute heart failure usually exacerbates the symptoms of depression. Once the heart failure is under control, the depressive signs and symptoms may abate. There are different pathological mechanisms of depression in cardiovascular diseases. The first is the psychological aspect associated with the development of life-threatening condition. The feeling of fear of death, anxiety about the future course of the disease, restrictions of physical activity, necessity of the invasive procedures usually cause anxiety and\or depression in patients in the acute phase of the disease. For the early post-myocardial infarction patients’ depression substrate more often is due to the impossibility of returning to normal physically active life, reduced work capacity, social adjustment difficulties and the impact of myocardial infarction on sexual activity. At the same time, despite the psychological mechanisms of depression, the dysfunction of the heart muscle also attributes to the development of depression. Myocardial dysfunction is usually observed in cardiovascular diseases (coronary heart disease, arterial hypertension, cardiomyopathy, inflammatory heart diseases, valvular lesions). Also the myocardial dysfunction in the form of heart failure is the final link in the chain of cardiovascular continuum. Any damage to the heart muscle leads to the increasing of the filling pressure in the heart chambers and thereby stimulates the increased activity of neurohumoral systems: the rennin-aldosterone-angiotensin, sympathetic nervous system, vasopressin and natriuretic peptides systems. Activation of neurohumoral systems aims to support the adaptation processes and homeostasis in heart failure syndrome but often causes harm. In the settings of the heart failure syndrome we should also mention the endogenous cannabinoid system, which as a system of the immediate response to stress, after the period of overstimulation becomes depleted causing a paradoxical effects. At the same time, depressive disorders are often accompanied by the hyperactivity of the hypothalamic- pituitary-adrenal axis, followed by increased excretion of cortisol in the bloodstream. Increased cortisol in this situation has a protective effect by mobilizing the body’s reserves. Interestingly, the higher levels of blood coagulation are observed in patients with cardiovascular disease and depression in comparison with patients without depression. Conclusions. The depression in terms of cardiovascular diseases may act as a risk factor for their development, it can be a cause of the heart muscle dysfunction, as well as be caused by psychological problems in consequence of the disease.